Role Conflict, Role Ambiguity, Independensi dan Kinerja Auditor - Bahtiar Effendi (STATERA: Jurnal Akuntansi dan Keuangan, 2019)
This study aims to examine the effect of role conflict, role ambiguity, and auditor independence on auditor performance. This type of research is quantitative research. The sampling technique was purposive sampling with a sample of 35 respondents from 14 Public Accounting Firms in the Jakarta. The data analysis technique used in this study is a multiple linear regression using the IBM SPSS Statistics version 24 program. The results show that: role conflict does not affect auditor performance, role ambiguity does not affect auditor performance, and auditor independence do not affect auditor performance.